Réponses

  • Omnes
  • Modérateur confirmé
2014-03-07T15:14:00+01:00
Salut,

 E(x) = 9-(2x-1)²

a)
E(x) = 9 - (4x² - 4x + 1 )
E(x) = 9 - 4x² + 4x - 1
E(x) = -4x² + 4x + 8
b)

 E(x) = 9-(2x-1)²
E(x) = 3² - (2x-1)²
E(x) = (3-(2x-1))(3+(2x-1))
E(x) = (3-2x+1)(3+2x-1)
E(x) = (4-2x)(2+2x)
--> Bonus (niveau 1ère) :

E(x) = (4-2x)(2+2x)
E(x) = 4(2-x)(1-x)

c)

E(1/2) = 
(4-2*(1/2) )(2+2*(1/2))= (4-1)(2+1) = 3*3 = 9

d)
E(x) = 0

(4-2x)(2+2x) = 0
4-2x = 0
-2x = -4
x = -4/(-2) = 2
2 + 2x = 0
2x = 2
x = 1


Bonne journée !